THE STUDY OF RELIGION IN DEPARTAMENT OF SOCIAL AND CULTURAL ANTHROPOLOGY VRIJE UNIVERSITEIT AMSTERDAM - Droogers, André; de Theije, Marjo; Versteeg, Peter (Debates do NER, 2007)
The authcrs of this artic analy the trajectory and the conterrporary moment of a group ofprofsors and reseamhers in Anthiopolcgy of Religion at the Departmmt of Social Anthropology at FreeUniversity of Amsterdam. They elabcrate a brief histcry of the constitution of the group in secord halfof the Century in the decades of 1960 and 1970, the field resrch were devebped in different locain the world, with theomtical marks also different. Nowadays there is an artiwlation of theresearches of the profsors and Ph.D. studmts in two big plDgrams.The first: "Between secularizationand sacralization", includes researches on the Dutth religious field from a qualitatiw methodologicalgrade The secord: "Careers of conversion and politics of culture", is dedicated on the study of theexpansionof charismatic and pentecostal Christianity in Holland and over the globe.